A simple approach to the synthesis of BCN graphene with high capacitance. (6th January 2015) - Dou, Shuo; Huang, Xiaobing; Ma, Zhaoling; Wu, Jianghong; Wang, Shuangyin
Abstract: Boron and nitrogen co-doped graphene (BCN graphene) was prepared through a simple thermal annealing approach in the presence of a single compound, melamine diborate. The as-prepared samples were characterized by scanning electron microscopy, transmission electron microscopy, x-ray photoelectron spectroscopy, Raman spectra and electrochemical techniques. The BCN graphene shows significantly enhanced specific capacitance due to boron and nitrogen co-doping, which permits higher overall doping levels.